STUDY ON DAMAGE ASSESSMENT FOR BEAM TYPE STRUCTURES BY VIRTUAL LOAD METHOD - LI CuiHong; YANG QiuWei; LIANG ChaoFeng; LU Chen (Jixie qiangdu)
The virtual load method is studied in this paper for damage assessment of beam type structures. The main advantage of this technique is that damage assessment can be accomplished by using only the vibration modes of the current structure. A series of virtual load vectors are constructed to obtain the same pure bending states for different segments of the beam. And then the curvatures of these segments loaded in pure bending are compared to identify the damage locations and extents. It was found that the proposed method is very suitable for damage assessment of those existing beam type structures.